Science in Carbon Economies: Debating What Counts in US Biofuel Governance. (February 2014) - Gillon, Sean
This paper analyzes the scientific practices that constitute carbon economies by rendering carbon countable, fungible, and governable. Examining US biofuel governance, I draw on field research and document and policy analyses to consider the roles state, private industry, and civil society actors play in negotiating scientific practice in biofuel governance and to explore the geographically uneven consequences of contrasting science–society configurations. This research illustrates the complex and contradictory roles of nature's quantification and state-supported science in carbon economies. Although nature's quantification as carbon was initially used as a technology of opposition and accountability to limit vested interest power and maintain biofuels' greenhouse gas reduction capacity, it ultimately served industry interests by focusing policy deliberation on technical issues industry deftly navigated and away from policy rationale, value conflict, and biofuels' broader social–ecological consequences. Drawing attention to state-supported environmental risk assessment and place-based approaches to integrating science and agriculture, this research describes multiple, conflicting modes of state scientific practice and emphasizes the importance of considering multiple scientific perspectives in climate change research and intervention. I argue that, rather than focusing on mitigating climate change through universal, carbon-focused science alone, future science–society configurations should include efforts to build institutional capacity for transformation and adaptation to confront uneven and changing social–ecological circumstances using site-specific scientific knowledge.